Influence of periaqueductal gray on other salience network nodes predicts social sensitivity. Issue 5 (3rd January 2022) - Rijpma, Myrthe G.; Yang, Winson F.Z.; Toller, Gianina; Battistella, Giovanni; Sokolov, Arseny A.; Sturm, Virginia E.; Seeley, William W.; Kramer, Joel H.; Miller, Bruce L.; Rankin, Katherine P.
Abstract: The intrinsic connectivity of the salience network (SN) plays an important role in social behavior, however the directional influence that individual nodes have on each other has not yet been fully determined. In this study, we used spectral dynamic causal modeling to characterize the effective connectivity patterns in the SN for 44 healthy older adults and for 44 patients with behavioral variant frontotemporal dementia (bvFTD) who have focal SN dysfunction. We examined the relationship of SN effective connections with individuals' socioemotional sensitivity, using the revised self‐monitoring scale, an informant‐facing questionnaire that assesses sensitivity to expressive behavior. Overall, average SN effective connectivity for bvFTD patients differs from healthy older adults in cortical, hypothalamic, and thalamic nodes. For the majority of healthy individuals, strong periaqueductal gray (PAG) output to right cortical ( p  < .01) and thalamic nodes ( p  < .05), but not PAG output to other central pattern generators contributed to sensitivity to socioemotional cues. This effect did not exist for the majority of bvFTD patients; PAG output toward other SN nodes was weak, and this lack of output negatively influenced socioemotional sensitivity. Instead, input to the left vAI from other SN nodes supported patients' sensitivity to others' socioemotional behavior ( p  < .05), though less effectively. The key role of PAG output to cortical and thalamic nodes for socioemotional sensitivity suggests that its core functions, that is, generating autonomic changes in the body, and moreover representing the internal state of the body, is necessary for optimal social responsiveness, and its breakdown is central to bvFTD patients' social behavior deficits. Abstract : This article describes the causal influence that salience network nodes have on each other, and shows that the directional output of the periaqueductal gray to other salience network structures is a predictor of socioemotional sensitivity. A key characteristic of this article is that we describe these network dynamics and brain–behavior relationships both in neurotypical humans, and in those with lesions in the salience network (i.e., patients with behavioral variant frontotemporal dementia), documenting inter‐individual variations of these network dynamics and their resulting impact on observed social sensitivity. These insights provide a framework for further investigation into the influence of variable neural dynamics on behavior.